Em defesa das crianças? A instrumentalização da democracia no discurso antigênero na Câmara dos Deputados e em espaços religiosos - Camargo, Bruna Quinsan (2021)
This dissertation seeks to analyze, through the Content Analysis of parliamentary speeches and videos of leaderships and religious public figures, the discourse on the so-called "gender ideology" in the Brazilian House of Representatives between 2015 and 2019. The analyzed period is marked by a moral conservative reaction that promoted censorship to debates about gender and sexuality, especially in schools, as a response to the gain of legitimacy of the feminist movement and the promotion of recognition policies by the State. The research development identified the values, principles and strategies that surround the parliamentarians, leaderships and religious public figures’ arguments that build the policy called antigender here. In order to prevent the advancement of sexual and reproductive rights and spread traditional morality in education, the lexicon of democracy is used as a tool and Christian values receive a secular camouflage. Therefore, the dedemocratizing political-religious action is legitimized in the public arena, enabling, as a consequence, the precariousness of lives and the perpetuation of inequalities and violence faced by historically subalternized groups, such as trans people, cisgender women and sexual dissidents.